Simone Weil’s aesthetics: beauty, attention, and commitment - Cascales Tornel, Raquel (Pensamiento. Revista de Investigación e Información Filosófica, 2025)
The thought of Simone Weil has gained increasing recognition within contemporary philosophy. However, while her contributions to political thought have been widely studied, her work in the field of aesthetics has received little attention, despite being a central axis that unifies her intellectual pursuits. This article aims to highlight the significance of this dimension by identifying three key elements of her aesthetic philosophy. First, it examines her notion of beauty, which reinterprets the classical concept and aligns it with contemporary perspectives that advocate for the recognition of beauty in all aspects of everyday life. Second, it explores her idea of disinterested attention, which, while rooted in Kantian aesthetics, offers an alternative to the modern subjectivization of aesthetic experience. Finally, it analyzes her conception of the artist and the worker, in which she expands the Romantic model of genius, proposing a vision that intertwines artistic creation with manual labor.